Diplomacia presidencial de Epitácio Pessoa: análise da política externa do presidente eleito: da Conferência da paz à volta ao Brasil - Lacerda, Matheus de Medeiros (2012)
Brazil was the only South American country to participate in the First World War. The participation in the conflict, as well as the help of the United States allowed him to occupy a prominent place in the Peace Conference at Versailles, where he had a satisfactory participation in resolving the issue of Brazilian coffee deposited in Germany and the issue of ex-vessel Germans held in Brazilian ports. Beyond economics, participation in the war allowed Brazil to play in resolving major issues in the committees and the Conference itself, putting into practice the standards of its foreign policy. However, the remarkable fact in the history of Brazilian diplomacy in the period was the election of the Chief of the Brazilian delegation in France, Epitácio Pessoa, as President of Brazil, even outside the country. This unique situation is examined here in a historical and theoretical perspective, with focus on Epitácio Pessoa as a decision maker, as diplomat, official candidate and president-elect during his stay in Europe until his return to Brazil, in order to demonstrate how its presidential diplomacy used the standards of the Brazilian’s First Republic foreign policy in order to maximize the gains for the new position of Brazil on the international stage, strengthening trade ties with the visited countries, emphasizing the historical ties and presenting Brazil as a land of opportunities in a world of social transformations. The active presidential diplomacy of Epitácio Pessoa, as a statesman accustomed to world affairs, realistic and conscious in their analysis of Brazil's position in international relations, gave Brazil a more universal character and a gain of prestige that changed the country's position in the concert of nations.